Opposing Democracy in the Digital Age The Yellow Shirts in Thailand - Sinpeng, Aim (Weiser Center for Emerging Democracies, 2021)
Opposing Democracy in the Digital Age is about why ordinary people in a democratizing state oppose democracy and how they leverage both traditional and social media to do so. Aim Sinpeng focuses on the people behind popular, large-scale antidemocratic movements that helped bring down democracy in 2006 and 2014 in Thailand. The yellow shirts (PAD-People's Alliance for Democracy) that are the focus of the book are antidemocratic movements grown out of democratic periods in Thailand, but became the catalyst for the country's democratic breakdown. Why, when, and how supporters of these movements mobilize offline and online to bring down democracy are some of the key questions that Sinpeng answers. While the book primarily uses a qualitative methodological approach, it also uses several quantitative tools to analyze social media data in the later chapters. This is one of few studies in the field of regime transition that focuses on antidemocratic mobilization and takes the role of social media seriously.